Perhitungan Koreksi Refraksi dalam Penentuan Tinggi Matahari Pada Awal Waktu Salat Asar - Saputra, A. Zuhrudin Hadi; Khazin, A. Mufti (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2024)
This article is the result of research related to the Calculation of Refractive Correction in Determining the Height of the Sun at the Beginning of the Asar Prayer Time